How a Bismuth(III) Catalyst Achieves Greatest Activation of Organic Lewis Bases in a Catalytic Reaction: Insights from DFT Calculations. Issue 3 (25th November 2020) - Babaahmadi, Rasool; Jalali, Mona; Smith, Jason A.; Yates, Brian F.; Ariafard, Alireza
Abstract: Density functional theory (DFT) was utilized to understand how bismuth(III) salts (BiX3 ) achieve greatest activation of organic Lewis bases in a catalytic reaction. It is reported in the literature that the BiX3 reactivity originates from its low lying Bi−X σ* orbital. In contrast to this belief, we will show here that for BiX3 to effectively serve as a catalyst, a p orbital of bismuth needs to be involved in activating organic substrates. Abstract : Lewis acid catalysis : Nucleophile RYH achieves the greatest activation by bismuth(III) salts (BiX3 ) if it directly coordinates to a Bi p orbital instead of a Bi−X σ* orbital. This condition is satisfied by isomerization of BiX3 (RYH) to a less stable see‐saw structure in which RYH occupies an equatorial position. The greater the activation of RYH, the lower the activation barrier to the release of H + or R + .